Phytochemical and Functional Properties of Philippine Sprouted Brown Rice (Oryza sativa L.) and its Potential as Base Ingredient for Functional Beverages - Bulatao, Rodel M.; Mabesa, Linda B.; Mabesa, Reynaldo C.; Merca, Florinia E. (2012)
This study aimed to evaluate the potential of sprouted brown rice (SBR) for the production of functional beverages. The rice samples consisted of NSIC Rc15, PSB Rc82, black rice and brown rice. SBR samples were characterized in terms of their nutritional, phytochemical and functional properties. Germination rate, length of sprouts, texture of cooked rice and total soluble solid (TSS) content were also determined. Black rice and PSB Rc82 produced the longest sprouts and had the highest germination rate. Sprouted black rice had the highest protein and fiber content while sprouted PSB Rc82 had the highest carbohydrate content. Sprouted black rice also contained the highest level of phytochemicals, except for antioxidant scavenging activity. Water absorption index, water solubility index and swelling power were higher in sprouted black rice and brown rice. Meanwhile, sprouted waxy rice had higher TSS content and softer cooked rice, producing smoother texture of rice beverages than nonwaxy rice. All beverages, except those produced from NSIC Rc15, were perceived to have flavorful and sweet taste. The acceptability of the rice beverages was comparable to one another. The results suggested that sprouted pigmented rice could be a potential source of natural antioxidants. Moreover, SBR from both white and pigmented rice varieties could be used to improve the nutritional and functional qualities of beverages.
Keywords: Brown rice